Inovasi Pendidikan Dalam Pengolahan Limbah Untuk Lingkungan Yang Bersih Di Padukuhan Derpoyudan - Althof, Muammar; Juliati, Santi; Alexander, Iham Arifin; Madani, Afifah Hanun; Noorzain, Tarina Putri; Wiranda, Zahra; Ni’ami, Addi Azka; Aziz, Abdul; Haliza, Alvera Violeta Nur; Rizqi, Zaidan Salma; Suswanta, Suswanta (Universitas Muhammadiyah Yogyakarta, 2025)
This Community Service Program (KKN) focuses on innovative organic waste management through the integration of maggot and azolla cultivation in Derpoyudan Hamlet, Tirtorahayu Village, Kulon Progo. The main issue faced by the community is a lack of awareness in waste management, leading to environmental pollution due to improper waste disposal. This program aims to provide a sustainable solution through the application of appropriate technology based on maggot and azolla. The methods used include socialization, training, and community mentoring in maggot cultivation as an organic waste decomposer and azolla as livestock feed and natural fertilizer. The results indicate an eighty percent increase in community awareness of organic waste management. Five households have implemented maggot cultivation, and two farmers have started utilizing azolla as fish feed. Additionally, the integration of automation technology in the maintenance system has improved cultivation efficiency. With these positive outcomes, this program is expected to continue and expand as a sustainable organic waste management model for the surrounding community